Course Life Scene The street Urban (Journal of Planner and Development, 2021)
The study of an urban street scene of the life cycle is one of the important things in urban scene studies and there are four vocabularys that are the basis for the life cycle of an urban scene and these vocabulary are (the street, transformation, land uses and urban scene). the first vocabulary addressed in the research is the street where street classes were studied and its classifications in terms of morphology and function and study of street standards in cities. The second term, are transformations, where the concept of transformation and its patterns and traditional factors that influence transformations were studied, which are represented (social, economic, religious and political). The singular land uses, it represents the urban land uses and its changes, they are the variable constants that depend on events inside the environment represented by the street. As for the last item concerned with the urban scene, it is the final image of the street, and this image is the outcome of events inside the street.